A Study on the Impact of Seasonal Demand on Revenue Patterns in FMCG at Dinshaw's Dairy Foods - Gajbhiye, Nibha Sanjeev; Tekade, Atul (Journal of Neonatal Surgery, 2025)
The study delves into the influence of seasonal demand fluctuations on revenue generation within the Fast-Moving Consumer Goods (FMCG) sector, with a particular focus on Dinshaw's Dairy Foods. In the FMCG industry, seasonal demand plays a crucial role in shaping the financial outcomes of businesses, affecting production, inventory management, and overall revenue. Through a combination of qualitative and quantitative research methodologies, the paper examines how varying consumer behaviour across different seasons impacts sales patterns, profit margins, and business sustainability for Dinshaw's Dairy Foods. By analysing historical sales data, seasonal marketing strategies, and market trends, the research uncovers key insights into how businesses can adapt their operations and strategies to optimize revenue during peak and off-peak seasons. The study further explores the role of promotional activities, product diversification, and supply chain management in mitigating the adverse effects of low demand periods. Findings suggest that effective forecasting, dynamic pricing, and targeted promotions can significantly enhance revenue generation despite seasonal volatility. The research contributes valuable recommendations for FMCG businesses looking to better align their operational strategies with consumer demand cycles, thereby improving financial stability and long-term growth. Ultimately, the study emphasizes the need for adaptive business models that can thrive amidst the challenges posed by seasonality in the FMCG industry